Performance benchmark of Si IGBTs vs. SiC MOSFETs in small-scale wind energy conversion systems - Hussein, Abdallah; Castellazzi, Alberto; Wheeler, Patrick; Klumpner, Christian (2016)
Modern power electronics devices based on SiC power MOSFETs technology become more demanding in the last few years. They show better performance over Si-IGBTs on renewable energy power conversion systems due to their higher switching frequency, higher temperature capability, higher power density and higher reliability. This paper presents a benchmarking of SiC-MOSFET and Si-IGBT power devices with the voltage rating of 1200V in 2-Level Full-Bridge (2L-FB) inverter for 10kW small scale wind turbine. By simulation, the inverter performance is evaluated in the presence of the wind speed distribution profile and the reference switching frequency value for SiC devices in this topology at this power level is determined. The results show that the SiC solution can improve the efficiency, save energy and reduce the size and cost due to high switching frequency and temperature capabilities.